2021
DOI: 10.3389/fcell.2021.625231
|View full text |Cite
|
Sign up to set email alerts
|

STIM2 Mediates Excessive Store-Operated Calcium Entry in Patient-Specific iPSC-Derived Neurons Modeling a Juvenile Form of Huntington's Disease

Abstract: Huntington's disease (HD) is a severe autosomal-dominant neurodegenerative disorder caused by a mutation within a gene, encoding huntingtin protein. Here we have used the induced pluripotent stem cell technology to produce patient-specific terminally differentiated GABA-ergic medium spiny neurons modeling a juvenile form of HD (HD76). We have shown that calcium signaling is dramatically disturbed in HD76 neurons, specifically demonstrating higher levels of store-operated and voltage-gated calcium uptakes. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 61 publications
0
39
0
2
Order By: Relevance
“…Additionally, the neuroprotective effect of SOCE inhibitor, EVP4593 was shown in the stabilization of high protein levels of both total HTT and STIM2 via regulation of their expression (Vigont et al, 2021). Interestingly, the severity of Ca 2+ influx via SOCE was independent of CAG repeat length between juvenile-and adultonset HD iPSCs-derived MSNs (Vigont et al, 2021). Additionally, a similar increase of voltage-gated calcium uptakes was observed in both juvenile-and adult-onset HD iPSCs-derived MSNs (Vigont et al, 2021).…”
Section: Trpc3mentioning
confidence: 94%
See 3 more Smart Citations
“…Additionally, the neuroprotective effect of SOCE inhibitor, EVP4593 was shown in the stabilization of high protein levels of both total HTT and STIM2 via regulation of their expression (Vigont et al, 2021). Interestingly, the severity of Ca 2+ influx via SOCE was independent of CAG repeat length between juvenile-and adultonset HD iPSCs-derived MSNs (Vigont et al, 2021). Additionally, a similar increase of voltage-gated calcium uptakes was observed in both juvenile-and adult-onset HD iPSCs-derived MSNs (Vigont et al, 2021).…”
Section: Trpc3mentioning
confidence: 94%
“…A recent publication by Vigont et al (2021) indicates that Ca 2+ signaling is highly elevated in iPSC-based GABAergic MSNs cultures from juvenile-onset HD patient containing 76 repetitions of CAG in mHTT. Authors specifically demonstrated -TRPC1-mediated elevation of Ca 2+ entry plays a role in adult hippocampal neurogenesis.…”
Section: Dysregulation Of Soce In Ipsc-derived Models From Hd Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction of HD cell models with gene editing techniques that can be used to validate the efficacy of therapeutic agents has been described in several articles (An et al, 2012(An et al, , 2014Xu et al, 2017;Dunbar et al, 2019;Ooi et al, 2019;Malankhanova et al, 2020a). Earlier studies have reported high calcium influx (Vigont et al, 2021) and ultrastructural synapse defects (Malankhanova et al, 2020b) in a HD cell model. Furthermore, the frequency of ultrastructural synapse defects is related to the number of CAG repeats (Morozova et al, 2018).…”
Section: Huntington's Diseasementioning
confidence: 99%